1996
DOI: 10.1101/gad.10.15.1930
|View full text |Cite
|
Sign up to set email alerts
|

Frequent provirus insertional mutagenesis of Notch1 in thymomas of MMTVD/myc transgenic mice suggests a collaboration of c-myc and Notch1 for oncogenesis.

Abstract: The MMTVD/myc transgenic mice spontaneously develop oligoclonal CD4+CD8 + T-ceU tumors. We used provirus insertional mutagenesis in these mice to identify putative collaborators of c-myc. We found that Notchl was mutated in a high proportion (52%) of these tumors. Proviruses were inserted upstream of the exon coding for the transmembrane domain and in both transcriptional orientations. These mutations led to high expression of truncated Notchl RNAs and proteins (86-110 kD). In addition, many Notchl-rearranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
202
2
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(220 citation statements)
references
References 63 publications
14
202
2
2
Order By: Relevance
“…All infected Tg mice analysed (n=47) developed oligoclonal thymomas. All analysed thymomas from both genotypes (except 2 Tg +/7 /Notch1 +/+ and 1 Tg +/7 /Notch1 +/7 mice) disseminated to the spleen, lymph nodes and sometimes in other organs (kidneys or the liver), in accordance to what was previously described (Girard et al, 1996). The mean latency of tumor appearance was 65 days in the Tg +/7 / Notch1 +/+ mice (n=21) and 67 days in the Tg +/7 / Notch1 +/7 mice (n=26) ( Table 1).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…All infected Tg mice analysed (n=47) developed oligoclonal thymomas. All analysed thymomas from both genotypes (except 2 Tg +/7 /Notch1 +/+ and 1 Tg +/7 /Notch1 +/7 mice) disseminated to the spleen, lymph nodes and sometimes in other organs (kidneys or the liver), in accordance to what was previously described (Girard et al, 1996). The mean latency of tumor appearance was 65 days in the Tg +/7 / Notch1 +/+ mice (n=21) and 67 days in the Tg +/7 / Notch1 +/7 mice (n=26) ( Table 1).…”
Section: Resultssupporting
confidence: 88%
“…We previously reported that the Notch1 gene was rearranged in more than 50% of T-cell lymphomas induced by Moloney MuLV infection of MMTV D /myc transgenic (Tg) mice (Girard et al, 1996). In these tumors, the proviruses were inserted upstream of exons coding for the transmembrane domain of Notch1 and were found in both transcriptional orientations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notch mutations appear to collaborate with a diverse collection of other proteins dysregulated in T-ALL. Retroviral oncogenesis in mice indicates a synergistic interaction between Notch1 and c-myc [162], E2A/ pbx [163] and dominant negative forms of Ikaros [164] to enhance development of T-ALL. Apart from Notch1, Notch3 was consistently expressed in human T-ALL and dramatically reduced in clinical remission [165].…”
Section: Notch and Leukemiamentioning
confidence: 99%